2017
DOI: 10.3390/biomedicines5030049
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer Cell-Based Selection: Overview and Advances

Abstract: Aptamers are high affinity single-stranded DNA/RNA molecules, produced by a combinatorial procedure named SELEX (Systematic Evolution of Ligands by Exponential enrichment), that are emerging as promising diagnostic and therapeutic tools. Among selection strategies, procedures using living cells as complex targets (referred as “cell-SELEX”) have been developed as an effective mean to generate aptamers for heavily modified cell surface proteins, assuring the binding of the target in its native conformation. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 103 publications
0
51
0
Order By: Relevance
“…The process generally includes counter-selection steps against unwanted targets in order to improve the aptamer selectivity. To date, many variants of SELEX have been described and applied to a wide range of different targets from purified proteins and small molecules to complex intact cells, tissues or live animals [ 13 ]. At the end of the selection, individual sequences are isolated by cloning or sequencing and are screened for the binding affinity and selectivity for the chosen target.…”
Section: Selex Technologies To Generate Nsclc Targeting Aptamersmentioning
confidence: 99%
See 1 more Smart Citation
“…The process generally includes counter-selection steps against unwanted targets in order to improve the aptamer selectivity. To date, many variants of SELEX have been described and applied to a wide range of different targets from purified proteins and small molecules to complex intact cells, tissues or live animals [ 13 ]. At the end of the selection, individual sequences are isolated by cloning or sequencing and are screened for the binding affinity and selectivity for the chosen target.…”
Section: Selex Technologies To Generate Nsclc Targeting Aptamersmentioning
confidence: 99%
“…Typically, aptamers are produced by a process of combinatorial chemistry known as systematic evolution of ligands by exponential enrichment (SELEX) [ 11 , 12 ] that can be applied to a wide range of targets, from purified proteins to whole living cells or tissues and organisms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers are developed in vitro via SELEX (Systematic evolution of Ligands by Exponential Enrichment), a method based on combinatorial chemistry which allows selection of high affinity DNA/RNA aptamers to the target molecule . Aptamers, for their unique ability to form secondary and tertiary structures, can recognize and bind a wide variety of target molecules, such as small molecules, proteins, cells and whole tissue . They also possess several advantages over antibodies, including higher stability, in vitro synthesis, easy chemical modification and lower immunogenicity.…”
Section: Figurementioning
confidence: 99%
“…[9,10] Aptamers, for their unique ability to form secondary and tertiary structures, can recognize and bind a wide variety of target molecules, such as small molecules, proteins, cells and whole tissue. [11] They also possess several advantages over antibodies, including higher stability, in vitro synthesis, easy chemical modification and lower immunogenicity. Therefore, aptamers are promising molecules for the development of specific, robust and cheaper sensing strategies with application in biomedicine.…”
mentioning
confidence: 99%
“…This result was not unexpected. While aptamers are known for their remarkable stabilities to bind their target over wide range of pH and temperatures (Catuogno & Esposito, 2017), it is also reported that significant pH changes can in fact reduce their detection sensitivities due to possible changes in their secondary structures, thus affecting target binding efficiency (Hianik, Ostatná, Sonlajtnerova, & Grman, 2007). This was likely the case for detection in orange juice (pH 4.0).…”
Section: Detection With Rca Signal Intensificationmentioning
confidence: 99%